2014
DOI: 10.1515/gps-2013-0113
|View full text |Cite
|
Sign up to set email alerts
|

A new green approach to Fenton’s chemistry using tea dregs and coffee grounds as raw material

Abstract: Fenton’s chemistry has long been useful in industry because of the power of hydrogen peroxide (HP), in the presence of ferrous iron (Fe2+), to produce a highly reactive free radical species capable of oxidizing aqueous materials. However, its application has been limited due to the rapid oxidation of ferrous iron. The rapid oxidation of ferrous iron limits the production of free radicals necessary for a powerful reaction. We developed two ‘green’ iron catalysts using used tea leaves (tea dregs) or coffee groun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In previous experiments, the results of an XPS survey revealed that both ferric iron (Fe 3+ ) and ferrous iron (Fe 2+ ) were present in the Fe-polyphenol catalyst but no zerovalent iron (nZVI) was present. Iron was present in the forms of Fe 2 O 3 /FeCl 2 and FeCl 3 14 . On the other hand, more than 98% of the iron released from the Fe-polyphenol catalyst was in the Fe 2+ form as detected by the phenanthroline method 15 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous experiments, the results of an XPS survey revealed that both ferric iron (Fe 3+ ) and ferrous iron (Fe 2+ ) were present in the Fe-polyphenol catalyst but no zerovalent iron (nZVI) was present. Iron was present in the forms of Fe 2 O 3 /FeCl 2 and FeCl 3 14 . On the other hand, more than 98% of the iron released from the Fe-polyphenol catalyst was in the Fe 2+ form as detected by the phenanthroline method 15 .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, more than 98% of the iron released from the Fe-polyphenol catalyst was in the Fe 2+ form as detected by the phenanthroline method 15 . The results of in vitro experiments showed that the Fe-polyphenol catalyst can be used to supply iron to leaf vegetables 12 and rice 13 , and in vitro experiments under laboratory conditions showed that when applied in conjunction with liquid H 2 O 2 , this catalyst could disinfect pathogens such as Escherichia coli 14 and Ralstonia solanacearum (see Supplementary Figs S2 , S3 , and S4 ) or remove methylene blue from water systems 15 . We proposed a mechanism involving the generation of hydroxyl radicals by the reaction between the iron catalyst and H 2 O 2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shi et al developed the Fenton reaction-assisted photodynamic inactivation method, a simple system that combines calcinated melamine sponges and Fe 2+ to inactivate Salmonella under light illumination [ 107 ]. Morikawa et al developed two “green” iron catalysts with reducing and chelating ability using tea leaves and coffee grounds [ 108 ]. This system with the catalytic Fenton reaction enhanced the degradation of the contaminants into harmless compounds and disinfection of Escherichia coli.…”
Section: Fenton Reaction In Foodmentioning
confidence: 99%